The Effect Of Brain Gym On Learning Concentration Levels In Grades 5 And 6 At Madrasah Ibtidahiyah Darul Arofah - Aldila Devita Niwa Cahyani (Penerbit Hellow Pustaka, 2025)
The level of concentration in learning is very much needed when the lesson begins, therefore students must concentrate when the teacher explains something, efforts to increase the level of concentration in learning are given brain gym movements to increase concentration and focus, reduce stress, improve memory, improve learning abilities, optimize eye and hand coordination, increase self-confidence and This study aims to determine the effect of Brain Gym on the level of concentration in learning in grades 5 and 6 at MI (madrasah ibtidahiyah) Darul Arofah. This type of research is pre-experimental with a one-group pre-post test approach with a population of 38 respondents, with a total sampling technique. The research instrument used a questionnaire sheet. And data analysis used the Wilcoxon Test, this brain gym movement consists of 6 movements. The results of the research that had been conducted before the brain gym movement in grade 5 and 6 children obtained a concentration level score of mostly less good 35 respondents (92%). After the brain gym movement was carried out in grade 5 and 6 children, the concentration level score was mostly good 17 respondents (44.73%), there was an effect of brain gym on the level of learning concentration in grade 5 and 6 children with a p-value of 0.001 <α 0.005.This research is expected to enable teachers to apply the brain gym movement to increase the level of learning concentration in children in grades 5 and 6. For further researchers, it is recommended to examine the differences between brain gym and breakfast to see whether breakfast or brain gym has an effect on the level of learning concentration. .